China's Global Political Economy Managerial Perspectives - Taylor, Robert; Jaussaud, Jacques (Routledge Studies on Comparative Asian Politics, 2018)
Much has been written about China's economy, as well as its business management system. China's Global Political Economy, however, is designed to bring together these two perspectives, serving to enhance our understanding of China's growing global role. Examining changes in the management strategies of foreign companies investing in China and Chinese enterprises doing business overseas, this book analyses China's political economy in the context of the Communist Party's changing policies. The introductory section begins by studying the aspects of Chinese economic growth as it impacts on domestic social issues and the projection of Chinese power abroad. Within this overall framework, it then goes on to critically assess the effects of foreign investment, business management strategies, human resource management, corporate social responsibility and the financial services sector. Arguing that the encouragement of consumption is a significant objective of the Chinese leadership, the last section is concerned with the importance of the food industry. This book will be of interest to students and scholars of Chinese business, management and international political economy, as well as policymakers and business practitioners.